The Effects of 8 Weeks Aerobic Training and Vitamins E & C Supplementation on the Plasma Levels of MMP-2 and MMP-9 in Patients with Coronery Heart Desease - E Karmi; R Shabani; F Rahmaniya; A Elmiye; M Rezagholizadeh (Armaghane Danesh Bimonthly Journal)
Background & aim: Coronary heart disease is one of the most important causes of death in most countries. Regular exercise and vitamin supplementation are useful solutions in improving cardiovascular diseases. The matrix metalloproteinase family plays an important role in the occurrence of cardiovascular diseases and the reconstruction of the vascular wall. The purpose of the present study was to investigate the effect of eight weeks of aerobic training with vitamin E and C supplementation on the plasma levels of matrix metalloproteinas2 and matrix metalloproteinas9 in patients with coronary artery disease.